Trends in the use of trichoscopy among dermatologists of Pakistan - Sajid, Fatima; Rizwan, Muneeza; Mushahid, Uzair; Rizwan, Shayan (Journal of Pakistan Association of Dermatologists, 2024)
Background Trichoscopy, also known as scalp dermatoscopy, is a non-invasive diagnostic tool used to identify hair morphological features not visible to naked eye. It is a relatively new field and despite establishing the importance of trichoscopy in clinical practice, it has repeatedly been identified as a practice gap among dermatologists. Â Objective To investigate the frequency of use of trichoscope by dermatologists in Pakistan. Â Methods A cross-sectional study including 265 practicing consultant dermatologists and resident dermatologists were included. Dermatologists were given an online questionnaire to be filled out.Â Descriptive statistics were calculated. Stratification was done. Chi square t-test was used to compare the age, sex and years of experience with the use of trichoscopy. P-value â‰¤0.05 was considered as significant with confidence intervals set at 95%. Â Results 9.4% dermatologists reported using trichoscope to diagnose hair disorders. This use was significantly higher with older age (p=0.019), but not with gender, clinical experience, job position, place of work or government versus private set up.Â Only 37.2% dermatologists were trained in using a trichoscope, where most were self-trained. Limited access to a trichoscope, absence of formal training and high costs of trichoscope were identified as the main hurdles to trichoscope use in Pakistan. Â Conclusion Trichoscope use is very limited in Pakistan often leading to inaccurate diagnosis and insufficient treatment of hair disorders. Access to formal training and low-cost trichoscopes are needed to bridge this important clinical gap.